Shuttle balance between lithiophilic functionalities substituted on conjugated polymers to improve lithium-ion diffusion and cycling stability of batteries - Kargude, Radhakisan; Javaregowda, Bharathkumar H.; Palani, Sathishkumar; Singh, Anup K.; Krishnamoorthy, Kothandam (Macromolecules, 2024)
Herein, we report the design and synthesis of i-Indigo and trans-1,2-di(2-thienyl)ethylene (TVT) comprising copolymers with various side chains that are used as anode-cum-binder in Li-ion batteries. The TVT disrupts the crystallinity, and the i-Indigo renders the handle for unsymmetrical substitution. Polymer P1 comprises alkyl chains on i-Indigo, whereas P2 comprises an alkyl chain and a chain with a urethane moiety as another side chain. Polymer P3 comprises i-Indigo with a urethane moiety and triethylene glycol as side chains. The i-Indigo in P4 is substituted with triethylene glycol and alkyl chains as side chains. These polymers were found to be amorphous with pi-pi stacking due to the extremely small torsional angle imparted by TVT moieties. All of these polymers showed comparable specific capacity while used as an anode in Li-ion batteries due to the presence of a common conjugated backbone. However, the battery metrics varied significantly while the current density of the batteries varied between 0.1 and 2.0 A g(-1). P1 and P2 showed a very close recovery of specific capacity at 0.1 A g(-1) before and after various current densities. However, polymers P3 and P4 did not recover from the specific capacity fading due to the presence of triethylene glycol side chain that degraded. Polymer P2 with an alkyl side chain and a chain with a urethane moiety showed stable performance over 2000 charge-discharge cycles. Contrary to this, the stability of polymers with triethylene glycol side chains decreased over 2000 charge-discharge cycles. Polymer P2 with a urethane side chain also showed improved Li-ion diffusion because the urethane moiety facilitated better Li-ion transport.

Synergistic effect of lactam and pyridine nitrogen on polysulfide chemisorption and electrocatalysis in lithium sulfur batteries - Javaregowda, Bharathkumar H.; Kargude, Radhakisan; Birajdar, Sarika; Shivankar, Bhavana; Krishnamurty, Sailaja; Jones, Lathe A.; Caruso, Rachel A.; Krishnamoorthy, Kothandam (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: Li-S battery; phenyl-diketopyrrolopyrrole; pyridine-diketopyrrolopyrrole

Long cycling stability imparted to li-ion batteries by conjugated polymers with low dihedral angles and high electron density on functional groups - Kargude, Radhakisan; Srinivasalu, Hari Haran; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam (ACS Applied Polymer Materials, 2025)
In conjugated polymers, dihedral angles at bonds connecting their monomers impact the polymers' properties such as the packing of the polymer chains, bandgap, and conductivity. These properties are expected to impact the performance of rechargeable Li-ion batteries because the Li-ion transport and conductivity of the polymers are two important parameters. To understand this, we designed and synthesized two polymers with two different dihedral angles. The polymer, Poly(EDOT-DPP), comprising diketopyrrolopyrrole (DPP) and ethylenedioxythiophene (EDOT) as monomers, showed a low dihedral angle of 2 degrees. On the other hand, the polymer, Poly(EDOT-i-Ind), comprising EDOT and i-Indigo (i-Ind) showed a dihedral angle of 17 degrees. Density functional theory (DFT) studies showed that the electron density at the carbonyl moiety of EDOT-DPP is higher than that of EDOT-i-Ind. This resulted in a higher Li+ binding energy of -3.665 eV for EDOT-DPP and a lower Li+ binding energy of -3.464 eV for EDOT-i-Ind. Battery electrodes were fabricated using either Poly(EDOT-DPP) or Poly(EDOT-i-Ind) with multiwalled carbon nanotubes as conducting fillers in the absence of any binders. The Li+ ion diffusion coefficient ( D Li + ) measured for the as prepared batteries based on Poly(EDOT-DPP) was found to be 3.9 x 10-19 cm2/s, which is slightly higher than that found for Poly(EDOT-i-Ind). However, after 2000 cycles, the D Li + increased by about two orders of magnitude for both polymers. Due to the low dihedral angle in the case of Poly(EDOT-DPP), the D Li + was found to be 21% higher than that of Poly(EDOT-i-Ind). The higher binding of Li+ ions with Poly(EDOT-DPP) and Li+ ion diffusion improved the specific capacity and cycling performance of batteries fabricated with this polymer. At a current density of 0.2 A/g, Poly(EDOT-DPP) showed a 39% higher specific capacity than the Poly(EDOT-i-Ind) polymer after 2000 cycles. The batteries also showed stable performance over 2000 cycles with an insignificant decrease in specific capacity.
Keywords: dihedral angle; diketopyrrolopyrrole; i-indigo; Li-ion battery; Li-ion transport

Modulation of lithium ion transport and cycling stability using rigid and flexible urethane moieties on the backbone of polymers - Kargude, Radhakisan; Rajendran, Prakash Babu; Kika, Sharmin Percy; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2025)
Graphite is the anode of choice for lithium-ion batteries. Due to volume change and poor conductivity of inorganic materials, they do not show comparable performance to that of graphite. Conjugated polymers are attractive because of their modularity and ease of synthesis. Herein, we report three polymers based on diketopyrrolopyrrole (DPP) as the anode. In an energy device, stored charges are due to a diffusive and capacitive component. Increasing the capacitive component is a challenge in both organic and inorganic systems. In our polymers, we installed urethane moieties that increase the capacitive component. The excellent Li+ ion transporting urethane moiety is part of the polymer chain. The Li+ ion transport is also impacted by the packing of the polymer chain. Therefore, the DPP units and urethane moieties are connected with either an alkyl chain, phenyl or biphenyl. The polymers with either alkyl or phenyl spacers showed stable cycling stability over 4000 charge-discharge cycles. On the other hand, the specific capacity of the batteries comprising a polymer with biphenyl started decreasing after 500 charge-discharge cycles. This is due to the solubility of the polymer in the battery electrolyte. The polymer with a phenyl spacer showed a higher Li+ ion diffusion coefficient due to the space generated between the polymer chains. The X-ray photoelectron spectroscopy analysis showed that the Li+ ions are bound to carbonyls, indicating the role of urethane in the charge transport. The polymer with an alkyl spacer showed a very high specific capacity of 600 mAh/g (1500th cycle) at a current density of 0.2 A/g, which is much higher than the theoretical capacity of graphite (372 mAh/g). The charge storage in all these polymers is dominated by a capacitive component, with the highest metric of 81% shown by a polymer with an alkyl spacer.
Keywords: Cycling stability; diketopyrrolopyrrole; high capacity; lithium-ion battery; non-conjugatedpolymer; urethane